2020
DOI: 10.1371/journal.pone.0240137
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness cognition, assessment, and promotion: A cross-sectional study in Taiwan

Abstract: Introduction Many health organizations have promoted the importance of the health-related benefits of physical fitness and physical activity. Studies have evaluated effective public health practice aiming to understand the cognition of physical activity among youths and adolescents. However, studies investigating the level of cognition and knowledge of physical fitness among Asian adults are lacking. Purpose This study aimed to investigate the self-awareness level of physical fitness and exercise prescription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
6
1
Order By: Relevance
“…The study of (Al-Jafar, 2015), (Zeyad, 2014), (Murray et al, 2014), (Bret, et.2014) [21,18,22,23], confirmed that improving physical fitness has a positive effect on maintaining a healthy human body free from disease and posture deformities, correcting part of wrong physical and movement behavioral habits, giving the individual a healthy and consistent figure, increasing the effectiveness of the immune system to resist diseases. These results contrast with the study of (Te-Wei Ho et al, 2020) [15], which revealed that there is a lack of awareness of health-related fitness, exercise prescription, and exercise planning progress, although most agree that physical, fitness and exercise are good for health.…”
Section: Discussing the First Questioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The study of (Al-Jafar, 2015), (Zeyad, 2014), (Murray et al, 2014), (Bret, et.2014) [21,18,22,23], confirmed that improving physical fitness has a positive effect on maintaining a healthy human body free from disease and posture deformities, correcting part of wrong physical and movement behavioral habits, giving the individual a healthy and consistent figure, increasing the effectiveness of the immune system to resist diseases. These results contrast with the study of (Te-Wei Ho et al, 2020) [15], which revealed that there is a lack of awareness of health-related fitness, exercise prescription, and exercise planning progress, although most agree that physical, fitness and exercise are good for health.…”
Section: Discussing the First Questioncontrasting
confidence: 82%
“…The results showed a severe absence of awareness of health-related fitness, exercise prescription, and exercise progress planning. 98% of people do not know the latest recommended guidelines for physical activity, although most agree that fitness and exercise are good for health [15]. (Olaf Prieske et al, 2019) conducted a study that aimed at examining physical fitness and psychological cognitive functioning associated to youth and middle-aged workers in light of physical and mental work activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result may be due to the underestimation of the value of physical activity and a healthy lifestyle [ 38 ]. In light of the Ho T-W (2020) study, insufficient awareness of the importance of physical activity and fitness for health may cause difficulties in self-assessment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences may result from the fact that rugby players focused on their training and organized their lives around them. Compared to the motivational functions of the goals of karate practitioners, boxers, football players and wheelchair basketball players (amateur level), no differences were observed on the perseverance scale, which was correlated only with sports experience [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data collected from the questionnaires include personal information and exercise habits. The “Physical Fitness 333 Plan” criteria were used to define regular exercise as promoted by the Ministry of Education in Taiwan, at least 30 min 3 times a week [ 15 ].…”
Section: Methodsmentioning
confidence: 99%